(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
This study examines academic internships as strategic pedagogical tools within university professionalization processes, approached from an experiential learning perspective. Using a qualitative methodology based on document analysis and semi-structured interviews with academic and technical-administrative staff, the institutional configurations of internships at the University of Costa Rica are characterized. The findings reveal high heterogeneity in their implementation, marked by tensions between curricular autonomy, nonexistent or fragmented regulations, and operational challenges in their management. While their formative potential to integrate theoretical and practical knowledge is recognized, the study concludes that their consolidation requires clear institutional guidelines, coordination between academic and administrative units, and a pedagogical approach aligned with graduate profiles. Strengthening these practices is seen as essential for ensuring contextualized, ethical, and socially committed professional training.